Effect of 5‐fluorouracil on excision repair cross‐complementing 1 expression and consequent cytotoxicity regulation in human gastric cancer cells. Issue 10 (16th July 2018) - Liu, Jing‐Lan; Huang, Wen‐Shih; Lee, Ko‐Chao; Tung, Shui‐Yi; Chen, Cheng‐Nan; Chang, Shun‐Fu
Abstract: Gastric cancer is the third leading cause of cancer mortality all over the world. The combination therapy of surgery with chemotherapy, that is, 5‐fluorouracil (5‐FU) and platinum‐containing anticancer drugs, is becoming a current clinical strategy for patients with gastric cancer because of the lower curative rate and higher cancer recurrence rate of patients treated with only surgery. However, the development of drug resistance in cancer cells is still the most challenge in clinical chemotherapy. Excision repair cross‐complementing 1 (ERCC1), an essential member of nucleotide excision repair system, recently has been suggested to be a predictive biomarker of treatment evaluation and might affect the outcomes of chemotherapy. Thus, this study was aimed to investigate whether ERCC1 expression could be regulated, and its role in gastric cancer cells treated with 5‐FU and the underlying mechanism. Human AGS gastric cancer cells were used in this study. It was shown that ERCC1 expression could be upregulated in AGS cells treated with 5‐FU and this upregulation could subsequently attenuate the cytotoxicity of 5‐FU in AGS cells. Moreover, 5‐FU–upregulated ERCC1 expression was regulated by extracellular signal‐regulated kinase (ERK) 1/2 and p38 signaling through activating the transcription factor c‐jun/activator protein (AP)‐1. These results indicated the role of ERCC1 in the development of drug resistance to 5‐FU in AGS cells. The mechanism elucidation concerning the ERK1/2 and p38 kinases and transcription factor c‐jun/AP‐1 might contribute another idea to the development of chemotherapy strategy for the gastric cancers in the future. Abstract : We demonstrated that ERCC1 expression could be upregulated and subsequently affect the cytotoxicity in AGS gastric cancer cells under 5‐FU treatment. Moreover, this upregulation of ERCC1 expression was regulated by ERK1/2 and p38 signaling and transcription factors c‐jun/AP‐1.